2013
DOI: 10.1016/j.mib.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans constitutes an ideal model organism to unravel the contribution of cellular aging to the virulence of chronic infections

Abstract: Aging affects all organisms, from unicellular yeasts to multicellular humans. Studies in model organisms demonstrate that the pathways that mediate the two forms of aging, replicative and chronological, are highly conserved. Most studies are focused on the effect of aging on an individual cell rather than a whole population. Complex longevity regulation, however, makes aging a highly adaptive trait that is subject to natural selection. Recent studies have shed light on the potential relevance of aging in funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 61 publications
2
16
0
3
Order By: Relevance
“…These cells are 30 – 50 μm large and polyploid. A less dramatic, but nonetheless significant and consistent cell size enlargement, is observed in the course of replicative aging of C. neoformans cells (Bouklas et al, 2013). …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These cells are 30 – 50 μm large and polyploid. A less dramatic, but nonetheless significant and consistent cell size enlargement, is observed in the course of replicative aging of C. neoformans cells (Bouklas et al, 2013). …”
Section: Introductionmentioning
confidence: 75%
“…However, recent studies in pathogenic fungi, such as Candida albicans (Fu et al, 2008) and Cryptococcus neoformans (Bouklas et al, 2013; Cordero et al, 2011; Jain et al, 2009a) have focused on other aspects and revealed effects of aging on phenotypic variation in these pathogens. Specifically, studies have investigated how age-related phenotypic changes alter virulence-associated traits and change host pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bu alanda, özellikle S. cerevisiae ile yapılan çalışmalar sırasında kronolojik yaşlanmanın enfeksiyonda virulans üzerine etkisi de araştırılmıştır. Yaşlanan mantarda oluşan fenotipik değişmele-rin, bazı durumlarda patojen için yarar sağlaya-bileceği yönünde yayınlar vardır (31) .…”
Section: Cryptococcus Neoformans'da Patojenli̇ği̇n Evri̇mi̇unclassified
“…Devleşme (gigantizm), invivo oluştuğu gibi kül-türlerde de saptanmıştır ve dev hücrelere, özel-likle, eski kültürlerde rastlanması, bu hücrelerin oluşmasının yaşlanmaya bağlı bir olay olduğuna işaret etmektedir (31,32) . Dev hücrelerin, mantarın konakta devamlı kalmasına (persistans) ve sonuçta latent yaşama ve hastalığın nükslerine (yinelemelerine) yol açabileceği bildirilmiş-tir (31) .…”
Section: Cryptococcus Neoformans'da Patojenli̇ği̇n Evri̇mi̇unclassified
See 1 more Smart Citation